Withdrawal of antihypertensive therapy in people with dementia: feasibility study - van der Wardt, Veronika; Burton, Jennifer, K.; Conroy, Simon; Welsh, Tomas (Biomed Central, 2018)
Background: This study explored the feasibility of a randomised controlled withdrawal trial of antihypertensive medication in normotensive people with dementia. Feasibility aspects included response, recruitment, exclusion and drop-out rates, suitability of outcome measures, acceptability of study procedures and an indicative economic evaluation for a randomised controlled trial.